Attitude and Practice of Tobacco Use Among Students in Tertiary Institutions in Kogi State, Nigeria - Onyekwere, O.K; Ononuju, Amaka Harry; Atuluku, G (International Journal of Human Kinetics, Health and Education, 2023)
This paper x-rays the attitude and practice of tobacco use among students in tertiary institutions in Kogi State, Nigeria. Four specific objectives were formulated with two research questions. Two null hypotheses were also postulated to guide the study. Descriptive survey research design was used for the study. The population of the study consisted of 31600 undergraduates in the selected tertiary institutions in Kogi State. The sample size consisted of 395 undergraduate students. Structured questionnaire was the instrument used for data collection. Face validity of the instrument was established by three experts from the Department of Human Kinetics and Health Education, University of Nigeria, Nsukka. Reliability of the instrument was established. Cronbach-alpha statistics was used to determine the reliability of section B on attitude while split-half reliability test (Spearman-Brown correlation formular) was used to establish the reliability index of section C on practice. After computation, a reliability coefficient of .079 was obtained for the instrument and adjudged reliable for use. Statistical package for social sciences version 22 was used for data analysis. Percentage and standard deviation were used in answering the research questions. The t-test and chi-square statistics were used in testing the hypotheses. Results of the study indicate that students in tertiary institutions had negative attitude towards tobacco use (mean score of 2.37); a good proportion (61.3%) of the students in tertiary institutions had practiced tobacco use. Furthermore, no significant difference was found to exist between students of various ages in their attitude (t-cal = .0174, df =393, p-value = .0596) and practice (χ2 =.0981, df =1, p-value =.539) of tobacco use. Based on the findings, recommendations such education regarding smoking, emphasizing on its negative consequences, should begin early in the primary schools and should be part of the primary school curriculum and students should be taught ways to say ―no‖ to tobacco use, were made.